APPRAISAL SYSTEM ANALYSIS IN ALADDIN’S DIALOGUES AS THE MAIN CHARACTER IN ALADDIN 2019 MOVIE - Asya Durrotun Nafisah; Ujang Suyatman; Deuis Sugaryamah (CALL, 2020)
Attitude have to do with evaluating things, people’s characters, and their feelings. Attitude can be identified not only from the dialogues used by people in their daily life interaction, but also from the characters’ dialogues in a movie. This research takes attitude and its language functions in Aladdin as the main character in Aladdin 2019 movie. This research focuses on; 1) What attitudes are revealed from Aladdin, the main character in Aladdin 2019 movie? 2) What language functions of Aladdin’s attitude in Aladdin 2019 movie? This research use qualitative method. There are two types of data, they are audio visual and document; Aladdin 2019 movie and its movie script. Technique of collecting data in this research use the audio visual documentation study technique and the researcher conducted mixed stages from some of the theories of analyzing data. To analyze data, researcher uses Appraisal System theory by J.R Martin, David Rose, and P.R.R White. The result of this research shows; 1) Aladdin as the main character in Aladdin 2019 movie revealed three types of attitudes; affect, judgment, and appreciation with 2) Aladdin’s attitude revealed five language functions from seven language functions by M.A.K Halliday; representational function, interactional function, personal function, heuristic function and regulatory function. Though, all types of attitude revealed in the movie, yet the most salient attitude Aladdin shown is positive appreciation, and the language used in his expressions has representational function.Keywords: Appraisal System, Attitude, Affect, Judgment, Appreciation, Aladdin.